2018
DOI: 10.1088/1361-6463/aadaa1
|View full text |Cite
|
Sign up to set email alerts
|

Spokes in high power impulse magnetron sputtering plasmas

Abstract: High power impulse magnetron sputtering (HiPIMS) is a deposition technique where a metal magnetron target is sputtered in a high density plasma to synthesize thin layers with superior properties on a substrate material. These plasmas are characterised by short pulses in the range of 50 µs to 200 µs and very high peak powers in the range of several kW/cm 2 per target area. The understanding of these dynamic plasmas is of upmost interest for the further development of this coating technique. Fast camera measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 67 publications
6
59
0
Order By: Relevance
“…We can name this process a growth-transport instability. Such "coupled processes" instability can be actually an interesting analogue of the ionization-movement instabilities observed as fast "spokes" in closed-drift (E × B drift) devices such as magnetrons [31][32][33] or Hall thrusters [34,35] but at a much longer timescale. However, we should admit that details of these phenomena remain unclear at present and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We can name this process a growth-transport instability. Such "coupled processes" instability can be actually an interesting analogue of the ionization-movement instabilities observed as fast "spokes" in closed-drift (E × B drift) devices such as magnetrons [31][32][33] or Hall thrusters [34,35] but at a much longer timescale. However, we should admit that details of these phenomena remain unclear at present and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing feature of experiments on × devices is that spokes do not always rotate in the × direction. Retrograde motion (in the − × direction) has also been observed in the low current regime of HiPIMS or in direct current (DC) magnetrons 23,24 .…”
mentioning
confidence: 92%
“…Rotating spokes have also been observed in Hall thrusters [17][18][19][20] and in pulsed planar magnetrons used in plasma processing (HiPIMS, for High Power Impulse Magnetron Sputtering) 1,21 . In some papers on Hall thrusters 17 or magnetrons 22 the CIV concept has been invoked to explain the presence of rotating spokes but there is no consensus on the physics of the rotating spokes in spite of important recent progress in the diagnostic and qualitative interpretation of these phenomena 23,24 . An intriguing feature of experiments on × devices is that spokes do not always rotate in the × direction.…”
mentioning
confidence: 99%
“…The goal of this work is to offer new insights into a particular experimental configuration that could lead to the formation of filaments and to motivate continuous experimental studies. Although the motivation of this work is in the use of magnetized CCPs in the study of dusty plasmas, cross-magnetic field transport is also an important phenomenon in many applications of low temperature plasmas, such as magnetrons 24 and Hall effect thrusters. 25 In this work, we have found that the filaments are quasistationary structures that originate from statistical variations in the local plasma potential and charging of surfaces.…”
Section: Introductionmentioning
confidence: 99%